Analisis b-value Gempabumi Menggunakan Metode Gutenberg-Richter Berdasarkan Estimasi Maximum Likelihood Di Daerah Sulawesi Utara - Reski Maulinda; Tri Kusmita; Herman Aldila; Triani Triani (Jurusan Fisika, Universitas Bangka Belitung, 2024)
Sulawesi is an area prone to earthquakes. This is because the Sulawesi region is flanked by three main plates, namely the Pacific Ocean plate moving westward, the Australian Continental Plate moving northward, and the Eurasian Plate moving south-southeast. This situation causes a high level of seismicity in the Sulawesi region. The Sulawesi region has a fairly complex tectonic setting so that the activity of earthquakes in the Sulawesi region is also interesting to study. The level of seismicity depends on the degree of fragility of the rock (b-value) and the distribution of earthquakes in the region. This research was conducted to determine the b-value of earthquakes in the North Sulawesi region. The method used for this research is the Gutenberg-Richter method based on the Maximum Likelihood estimation. Maximum Likelihood Estimation is a method used to statistically calculate earthquake activity parameters. The software used are ArcGIS and Microsoft Excel. The research was conducted in North Sulawesi with coordinates 118° East - 125° East 1° North Latitude - 6° South Latitude. The data used is earthquake catalog data obtained from BMKG with earthquake data for a period of 10 years (2012-2021). Based on the results of the analysis of the distribution of seismicity based on magnitude, it is more towards the Sulawesi Sea and the distribution of seismicity based on depth is shallow. The result of calculating the b-value is 0.3537 and the a-value is 3.0932. It can be concluded that the North Sulawesi region has a fairly large chance of an earthquake occurring